Commercial gaming devices for stroke upper limb rehabilitation: A systematic review. Issue 4 (24th March 2014) - Thomson, Katie; Pollock, Alex; Bugge, Carol; Brady, Marian
<x xml:space="preserve">Abstract</x> Background and purpose Rehabilitation using commercial gaming devices is a new concept for stroke care. Commercial gaming devices such as Nintendo Wii or Sony PlayStation encourage high repetition of arm movements and are being introduced into some clinical settings. The evidence base for gaming use in rehabilitation is growing rapidly and there is a need to systematically synthesise research. Our review aims to integrate evidence on how gaming is being used, explore patient/therapist experience and synthesise evidence of effectiveness. Summary of review An integrative systematic review was undertaken searching Cochrane Central Register of Controlled Trials (2013), Medline (2013), Embase (2013) and twelve additional databases. Two review authors independently selected studies based on pre‐defined inclusion criteria, extracted data and assessed risk of bias. Nineteen studies including 215 patients met inclusion criteria. Studies were typically small scale feasibility studies using a range of research designs, limiting the ability to reach generalised conclusions. Results have been tabulated (activities of daily living, upper limb function/ movement) and qualitative themes identified. Findings suggest that most patients enjoy using commercial gaming and can tolerate 180 mins per week without significant adverse effects. A trend towards improvement was noted for upper limb function/ movement. Few studies recorded outcomes related to activities of daily living or focused on understanding patients' experiences of this intervention. Conclusion Commercial gaming can provide high intensity upper limb practice however there is insufficient high quality evidence to reach generalisable conclusions about risks or benefits on activities of daily living or upper limb function/movement.